OSIOLOGI PADA KELAS XI IPS 2 DI SMA NEGERI 2 LENGAYANG KABUPATEN PESISIR SELATAN TAHUN 2014 - DELLA, DIDO PRAMAI (Pendidikan Sosiologi, 2014)
This study originated from the reality in SMA 2 Lengayang that activity andstudent learning outcomes is low, it can be seen that most of the teachers topresent course material using conventional methods. One way to overcome this isto implement such a media reality. This study aims to determine whether thelearning outcomes of students using the media sociology reality is better than theresults of studying sociology students taught with conventional teaching. Thisresearch is a quantitative and experimental research type. The population of thisstudy is a class XI IPS 1, XI IPS 2, and 3 SMA XI IPS 2 Lengayang. The sampleswere selected by random sampling technique for this study population washomogeneous.The theory used in this study is cognitive. The results of theanalysis based on the count â¥ x2 x2 table is 34.64> 5.991, then Ho is rejected andHa accepted that a significant meaning. Whereas the results studied sociology atthe experimental class and control class there are significant differences betweenthe two classes, where after the data analysis using the chi-square formula isobtained that the experimental class higher than the control class. averageexperimental class is 77 and the average of the control class is 32, and thestandard deviation of the experimental class 7.78 9.17 grade control.